2017
DOI: 10.1111/imr.12520
|View full text |Cite
|
Sign up to set email alerts
|

Tim‐3 and its role in regulating anti‐tumor immunity

Abstract: Summary Immunotherapy is being increasingly recognized as a key therapeutic modality to treat cancer and represents one of the most exciting treatments for the disease. Fighting cancer with immunotherapy has revolutionized treatment for some patients and therapies targeting the immune checkpoint molecules such as CTLA-4 and PD-1 have achieved durable responses in melanoma, renal cancer, Hodgkin’s diseases and lung cancer. However, the success rate of these treatments has been low and a large number of cancers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
541
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 676 publications
(551 citation statements)
references
References 124 publications
(268 reference statements)
3
541
0
7
Order By: Relevance
“…One feasible approach is to identify and block additional inhibitory receptors on hyporesponsive CD8 + T cells to augment antitumor function. Additional inhibitory receptors such as TIM‐3, LAG‐3, BTLA, Vista and B7‐H4 have been identified on chronically stimulated T cells and antibodies that block the respective ligands suggest these pathways contribute to CD8 + T‐cell dysfunction in functionally independent manners . Recent preclinical studies have identified CD96 and TIGIT as co‐inhibitory Ig superfamily receptors which function on lymphocytes to counterbalance the costimulatory CD226.…”
Section: Discussionmentioning
confidence: 99%
“…One feasible approach is to identify and block additional inhibitory receptors on hyporesponsive CD8 + T cells to augment antitumor function. Additional inhibitory receptors such as TIM‐3, LAG‐3, BTLA, Vista and B7‐H4 have been identified on chronically stimulated T cells and antibodies that block the respective ligands suggest these pathways contribute to CD8 + T‐cell dysfunction in functionally independent manners . Recent preclinical studies have identified CD96 and TIGIT as co‐inhibitory Ig superfamily receptors which function on lymphocytes to counterbalance the costimulatory CD226.…”
Section: Discussionmentioning
confidence: 99%
“…TIM-3 mediates its suppressive activity on immune cells via its ligands that include phosphatidylserine, CEACAM-1 and the widely expressed ligand galectin-9 23,24 . TIM-3 is expressed on activated T cells and its signaling on cytotoxic T cells leads to an exhausted phenotype, characterized by a reduction in proliferation, decreased production of effector cytokines and apoptosis of effector T cells 25 . In addition, TIM-3+ TILs can co-express PD-1, with blockade of both receptors leading to a more pronounced tumor regression than either agent alone, at least in pre-clinical studies 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies against CTLA‐4 and PD‐1 have been used to treat many immune disorders . Tim‐3 is considered a next‐generation checkpoint inhibitor with therapeutic potential . A previous report has shown that Tim‐3 expression is significantly upregulated in patients who are resistant to PD‐1 antibody treatment .…”
Section: Introductionmentioning
confidence: 99%